On the influence of mountain and heritage tourism in Georgia: the exemplary case of Ushguli - Applis, Stefan (ERDKUNDE, 2019)
This study centres on the village community of Ushguli, located in the Upper Svaneti region in the north of Georgia. After attaining UNESCO World Heritage status in 1996, and benefiting since around 2010 from the establishment of secure state structures and systems, Ushguli has seen an incremental rise in tourism. Thus far, it has been relatively unprepared for meeting the interests and needs of visitors and coping with the diversity characterising modern lifestyles. The encounter and in many instances clash of interests between villagers and tourists is correspondingly difficult to channel and manage; visitor numbers are continuously growing, due at least in part to local residents’ efforts to advance their economic goals. Ushguli therefore represents a space offering ideal experimental conditions for the exploration of tourism as a strategy for overcoming economic and social crisis and of its effects on preexisting spatial, economic, environmental and social structures, against a backdrop of change to material and immaterial objects driven by various stakeholders. This article provides an overview of the specific focus of this study, commenced in 2017 and planned to cover a duration of several years, and of the research approach taken, as well as outlining central findings.